(untitled) (Sociologisk Forskning, 2006)
This article reviews and considers how the methodology of grounded theory has developed in the light of the profound critique it has attracted during recent decades. Four types of critique are examined, representing diverse meta-theoretical positions such as critical realism, constructivism and postmodernism. Agreements and differences are described which indicate a consensus among researchers, irrespective of conflicting philosophical positions, that grounded theory is a workable approach for doing research. In particular, the discussion emphasizes how promoters of these perspectives deal with the basic aim of grounded theory to develop empirically based theories. A tendency to replace theory with narrative or other limited substitutes such as depiction is problematized. Questions of validation, evaluation, and legitimization of grounded theory, extended to include qualitative research in general, are touched upon. In conclusion it is argued that grounded theory, due to transformations and modifications inspired by positive critique, is better suited to meet todays demand for complex and reflexive research methodologies.